Density Profiles of Well‐Defined Poly(methyl 2‐propenyl ether) (PMPE) Near Water Interface. Issue 1 (April 2015) - Oda, Yukari; Kawaguchi, Daisuke; Hirata, Toyoaki; Yamada, Norifumi L.; Kanaoka, Shokyoku; Aoshima, Sadahito; Tanaka, Keiji; Kitayama, Tatsuki; Aoshima, Sadahito; Kamigaito, Masami
Summary Poly(methyl 2‐propenyl ether) (PMPE) is structually different in terms of the presence of an α‐methyl group on the main chain from poly(vinyl methyl ether) (PVME), the phase behaviors of which have been widely characterized with polystyrene (PS) and water. Due to the incorporation of the α‐methyl group, PMPE is immiscible with both PS and water. These results encouraged us to investigate a PMPE/water interface more closely. Thus, the density profiles of PMPE in the vicinity of the water interface were probed by neutron reflectivity (NR) measurement. Even in the presence of the α‐methyl group on the main chain, PMPE slightly swelled near the water interface. The obtained results will give us an insight into a better design and construction of the polymers for several bioapplications.